Self-Efficacy for HIV Prevention among Refugee Hispanic Women in South Florida - Cianelli, Rosina (J Immigr Minor Health, 2017)
The number of refugees increased in recent years due to factors worldwide, including violence, wars, political strife, and natural disasters. Refugees who are Hispanic women (RHW) in South Florida are a vulnerable population at risk of acquiring HIV infection. Although studies have shown a relationship between self-efficacy for HIV prevention and behavior changes, none have studied RHW. The purpose of this study was to assess whether predictors suggested by the literature were related to self-efficacy for HIV prevention in a sample of RHW. The study is a secondary analysis that uses baseline data from a randomized controlled experimental study, SEPA. A total of 99 refugee Hispanic women from South Florida, 18–50 years of age, participated in the study. There were two predictors of sefl-efficacy. HIV knowledge was positively related to self-efficacy, and living with a partner was inversely related to self-efficacy for HIV prevention. Culturally competent sexual health education interventions in this population may impact self-efficacy for HIV prevention.